The haunted mask - Stine, R. L.; Gonzalez, Maddi (Goosebumps graphix., 2024)
Carly Beth needs the perfect Halloween mask. One that will scare everyone she comes across -- including her annoying little brother and the bullies from her school. A visit to a strange costume store provides just the right one. An ugly green, with fierce fangs, the mask makes Carly Beth feel powerful and scary. But when the mask won't come off, will the monster take over?